2017
DOI: 10.3389/fimmu.2017.01067
|View full text |Cite
|
Sign up to set email alerts
|

Mind the Gaps in Tumor Immunity: Impact of Connexin-Mediated Intercellular Connections

Abstract: Gap junctions (GJs)-mediated intercellular communications (GJICs) are connexin (Cx)-formed plasma membrane channels that allow for the passage of small molecules between adjacent cells, and are involved in several physiopathological processes, including immune responses against cancer. In general, tumor cells are poorly coupled through GJs, mainly due to low Cx expression or reduced channel activity, suggesting that Cxs may have tumor suppressor roles. However, more recent data indicate that Cxs and/or GJICs m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
31
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 29 publications
(31 citation statements)
references
References 195 publications
0
31
0
Order By: Relevance
“…In non-tumor tissues Cx31 expression has been identified in keratinocytes, the small intestine, and the colon (45,46). Although roles for various connexins as oncogenes and/or tumor suppressors have been described (39,40), the function of Cx31 in tumorigenesis has not been established.…”
Section: Main Textmentioning
confidence: 99%
“…In non-tumor tissues Cx31 expression has been identified in keratinocytes, the small intestine, and the colon (45,46). Although roles for various connexins as oncogenes and/or tumor suppressors have been described (39,40), the function of Cx31 in tumorigenesis has not been established.…”
Section: Main Textmentioning
confidence: 99%
“…In this line, since more than five decades ago, it is known that cancer cells isolate themselves from their cellular environment down-regulating GJIC [ 49 ]. Indeed, aberrant Cx43 expression and its mislocalization, which leads to reduced GJIC, are frequent in different tumors, including melanoma, and predict cancer patient outcome [ 19 , 50 ]. Numerous evidences have shown that Cx43 suppresses tumors via different heterotypic (cancer cell-immune cell or cancer cell-stromal cell) GJICs, as we previously reviewed [ 19 , 23 ].…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, aberrant Cx43 expression and its mislocalization, which leads to reduced GJIC, are frequent in different tumors, including melanoma, and predict cancer patient outcome [ 19 , 50 ]. Numerous evidences have shown that Cx43 suppresses tumors via different heterotypic (cancer cell-immune cell or cancer cell-stromal cell) GJICs, as we previously reviewed [ 19 , 23 ]. Indeed, Cx43-CJICs have been implicated in different antitumor roles that affect the cancer-immunity cycle ( Figure S4 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Gap junctions are intercellular channels that directly connect the cytoplasm of adjacent cells, allowing the passage of current and small signaling molecules[11,49]. A gap junction is composed of two connexons integrated into the plasma membranes of the connected cells forming a channel[50,51]. Each connexon is composed of 6 connexins.…”
mentioning
confidence: 99%